Best practice interventions to improve the management of older people in acute care settings: A literature review - Hickman, L.; Newton, Phillip; Halcomb, E.; Chang, E.; Davidson, Patricia (Blackwell Publishing Ltd, 2007)
Aim. This paper is a report of a literature review of experimental evidence describing interventions to manage the older adult in the acute care hospital setting. Background. Older people are increasingly being cared for in a system largely geared towards acute care. This approach is often inadequate to meet the needs of older patients with chronic and complex conditions. In response to these challenges, evidence-based interventions are required to improve health outcomes. Method. The MEDLINE and CINAHL databases and the Internet were searched using the keywords elderly, older, geriatric and aged care. Studies published between 1985 and 2006 were included if they reported, in English, a controlled trial of an intervention designed to improve the management of older adults in the acute care setting. The findings were synthesized using the method of a modified integrative literature review. Findings. Only 26 controlled trials met the inclusion criteria. The following elements of interventions appear critical in providing optimal health outcomes for older people admitted to acute care: (1) a team approach to care delivery either directly in a designated unit for older patients or indirectly using gerontological expertise in a consultancy model; (2) targeted assessment techniques to prevent complications; (3) an increased emphasis on discharge planning and (4) enhanced communication between care providers across the care continuum. Conclusion. A multidisciplinary team approach, using gerontological expertise, in acute care settings is recommended to improve the care of older patients. Care delivery should occur in a specially designed unit, with communication strategies that emphasize discharge planning.